Prenatal Hypoxia Induces Cl– Cotransporters KCC2 and NKCC1 Developmental Abnormality and Disturbs the Influence of GABAA and Glycine Receptors on Fictive Breathing in a Newborn Rat - Caravagna, Céline; Casciato, Alexis; Coq, Jacques-Olivier; Liabeuf, Sylvie; Brocard, Cécile; Peyronnet, Julie; Bodineau, Laurence; Cayetanot, Florence (Frontiers in Physiology, 2022)
Prenatal hypoxia is a recognized risk factor for neurodevelopmental disorders associated with both membrane proteins involved in neuron homeostasis, e.g., chlorid (Cl-) cotransporters, and alterations in brain neurotransmitter systems, e.g., catecholamines, dopamine and GABA. Our study aimed to determine whether prenatal hypoxia alters central respiratory drive by disrupting development of Cl- co-transporters KCC2 and NKCC1. Cl- homeostasis seems critical for the strength and efficiency of inhibition mediated by GABAA and glycine receptors within the respiratory network, and we searched for alterations of GABAergic and glycininergic respiratory influences after prenatal hypoxia. We measured fictive breathing from brainstem in ex vivo preparations during pharmacological blockade of KCC2 and NKCC1 Cl- co-transporters, GABAA and glycine receptors. We also evaluated the membrane expression of Cl- co-transporters in the brainstem by Western blot and the expression of Cl- cotransporter regulators BDNF and calpain. First, pharmacological experiments showed that prenatal hypoxia altered the regulation of fictive breathing by NKCC1 and KCC2 Cl- cotransporters, GABA/GABAA and glycin. NKCC1 inhibition decreased fictive breathing at birth in control mice while it decreased at 4 days after birth in pups exposed to prenatal hypoxia. On the other hand, inhibition of KCC2 decreased fictive breathing 4 days after birth in control mice without any change in prenatal hypoxia pups. The GABAergic system appeared to be more effective in prenatal hypoxic pups whereas the glycinergic system increased its effectiveness later. Second, we observed a decrease in the expression of the Cl- cotransporter KCC2, and a decrease with age in NKCC1, as well as an increase in the expression of BDNF and calpain after prenatal hypoxia exposure. All together, our data support the idea that prenatal hypoxia alters the functioning of GABAA and glycinergic systems in the respiratory network by disrupting maturation of Cl- homeostasis, thus contributing to long term effects by disrupting ventilation.